Pengaruh Soft-Selling Video Iklan Produk Marjan terhadap Niat BeliKonsumen melalui Perilaku Konsumen terhadap Iklan - Sinuraya, Yohanes Exspandio Perfecta; Pratama, Alzetrho Baja; Albari, Pascal Kharua (Westscience Press, 2025)
This study investigates the influence of Marjan’s soft-selling advertisement on consumers’ attitudes toward the ad and their purchase intention in Greater Tangerang. The main issue addressed is the effectiveness of soft-selling advertising in shaping emotional responses and consumer purchase decisions. A quantitative approach was applied by distributing questionnaires to 218 respondents who had seen Marjan’s Ramadan-themed advertisement. Data were analyzed using validity and reliability tests, multiple linear regression, and both partial and simultaneous significance tests. The results reveal that soft-selling advertising significantly affects consumers’ attitudes toward the ad, which in turn significantly influences their purchase intention. The narrative and emotional delivery used in the advertisement proved effective in creating a positive impression and increasing consumer interest. In conclusion, soft-selling is a relevant strategy to build emotional engagement with consumers, especially for seasonal products like syrup during Ramadan.